1979
DOI: 10.1159/000112451
|View full text |Cite
|
Sign up to set email alerts
|

NGF and Anti-NGF: Evidence against Effects on Fiber Growth in Locus coeruleus from Cultures of Perinatal CNS Tissues

Abstract: The present study examines whether the developing noradrenergic neurons of locus coeruleus depend on endogenous nerve growth factor (NGF) for nerve fiber production and if exogenous NGF stimulates fiber growth in this nucleus, using a collagen gel tissue culture technique. Locus coeruleus from perinatal rat brain was used in three culture experiments: (1) locus coeruleus, parietal cerebral cortex, and the superior cervical ganglion, prepared from newborn rats and cultured in different sectors of the same dishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Nerve growth factor, which strongly increased the density of cholinergic fibres and elevated the levels of cholinergic enzymes in septo-hippocampal co-cultures (G3hwiler et al, 1987, 1989), had no apparent morphological effect on the development of TH-positive cells in co-cultures of brainstem and hippocampus. This observation is consistent with previous studies on central noradrenergic cells in situ (Schwab et al, 1979) and in vitro (Dreyfus et al, 1980;Olson et al, 1979;Victorov et al, 1979). In variance to cholinergic fibres in septo-hippocampal co-cultures (Gahwiler et al, 1989;Gahwiler and Knopfel, unpublished observations), following several weeks in vitro TH-positive fibres originating in cultures of the LC were still present in the outgrowth areas where they formed whirl-like endings.…”
Section: Discussionsupporting
confidence: 94%
“…Nerve growth factor, which strongly increased the density of cholinergic fibres and elevated the levels of cholinergic enzymes in septo-hippocampal co-cultures (G3hwiler et al, 1987, 1989), had no apparent morphological effect on the development of TH-positive cells in co-cultures of brainstem and hippocampus. This observation is consistent with previous studies on central noradrenergic cells in situ (Schwab et al, 1979) and in vitro (Dreyfus et al, 1980;Olson et al, 1979;Victorov et al, 1979). In variance to cholinergic fibres in septo-hippocampal co-cultures (Gahwiler et al, 1989;Gahwiler and Knopfel, unpublished observations), following several weeks in vitro TH-positive fibres originating in cultures of the LC were still present in the outgrowth areas where they formed whirl-like endings.…”
Section: Discussionsupporting
confidence: 94%
“…About the same time that it was demonstrated that central catecholaminergic neurons do not respond to NGF (Konkol et al 1978;Schwab et al 1979;Olson et al 1979;Dreyfus et al 1980) and do not express NGF receptors (Schwab et al 1979), but that NGF is transported specifically from the hippocampus to septal cholinergic neurons (Schwab et al 1979), several laboratories reported that lesioning the septo-hippocampal pathway resulted in an ingrowth of perivascular sympathetic fibers into the hippocampus (Loy and Moore 1977;Stenevi and BjOrklund 1978;Crutcher et al 1979;Crutcher and Davis 1981). It was also demonstrated that only a fimbrial transection could trigger this reactive ingrowth of peripheral sympathetic nerve fibers.…”
Section: The Role Played By Fimbria Lesion Experiments In the Elucidamentioning
confidence: 99%
“…However, both the presence and potential physiological function of NGF in the central nervous system (CNS) has remained elusive (3). The characteristic responses of peripheral adrenergic neurons following NGF or anti-NGF antibody injection have not been observed after similar application into the CNS (4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%